2012
DOI: 10.1016/j.jpeds.2011.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Severe Vaso-Occlusive Painful Episode Frequency in Children and Adolescents with Sickle Cell Anemia

Abstract: Objective To identify factors associated with frequent severe vaso-occlusive pain crises in a contemporary pediatric cohort of sickle cell anemia (SCA)enrolled in a prospective study of pulmonary hypertension and the hypoxic response in sickle cell disease (SCD). Study design Clinical and laboratory characteristics of children with SCA who had ≥3 severe pain crises requiring health care in the preceding year were compared with subjects with <3 such episodes. Results Seventy-five children (20%) reported ≥3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 31 publications
7
72
0
Order By: Relevance
“…These data strongly suggest that HbF levels have a definitive, but small impact on the incidence rate of pain in children with SCA. Similar to previous vaso-occlusive pain studies [13, 14], we have validated that counting inpatient admissions for pain replicates the counting of pain episodes occurring predominantly in outpatient settings. These findings validate the use of vaso-occlusive pain resulting in hospitalization as a phenotype that can easily be obtained via an electronic medical record review.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…These data strongly suggest that HbF levels have a definitive, but small impact on the incidence rate of pain in children with SCA. Similar to previous vaso-occlusive pain studies [13, 14], we have validated that counting inpatient admissions for pain replicates the counting of pain episodes occurring predominantly in outpatient settings. These findings validate the use of vaso-occlusive pain resulting in hospitalization as a phenotype that can easily be obtained via an electronic medical record review.…”
Section: Resultssupporting
confidence: 76%
“…These findings validate the use of vaso-occlusive pain resulting in hospitalization as a phenotype that can easily be obtained via an electronic medical record review. Definitions of pain used in previous studies of this issue have been variable and have included self-reported pain [10], pain that lasted for two hours and required a physician visit [3], and pain that required hospitalization [14]. Each definition has unique attributes; however, in the case of self-reported pain or pain that requires a visit to a physician office, the challenges of ongoing data entry, coupled with validation of each event make these definitions challenging to use in a multi-center study.…”
Section: Resultsmentioning
confidence: 99%
“…However, the opposite trend was seen in patients, where the left insula's role in the salience network increased with age. It is known as SCD patients age, their chronic pain increases and their disease severity worsens (Darbari et al, 2012, Platt et al, 1994, Platt et al, 1991). This means the increased involvement of left insula in salience network could be a result of increased pain severity.…”
Section: Discussionmentioning
confidence: 99%
“…higher hemoglobin and lower reticulocyte count, LDH, AST and bilirubin) is associated with a SCD phenotype with more painful events. [42, 43] The lack of a generalized association of these laboratory parameters with our primary and secondary outcomes suggests hemolysis may not play a major role in the pain sensitivity as measured by our techniques. Other mechanisms may be linked to this increased pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%